On the valuation of fader and discrete barrier options in Heston's Stochastic Volatility Model - Susanne Griebsch; Uwe Wystup (Frankfurt School of Finance & Management, Centre for Practical Quantitative Finance (CPQF), 2008)
We focus on closed-form option pricing in Heston's stochastic volatility model, in which closed-form formulas exist only for few option types. Most of these closed-form solutions are constructed from characteristic functions. We follow this approach and derive multivariate characteristic functions depending on at least two spot values for different points in time. The derived characteristic functions are used as building blocks to set up (semi-) analytical pricing formulas for exotic options with payoffs depending on finitely many spot values such as fader options and discretely monitored barrier options. We compare our result with different numerical methods and examine accuracy and computational times.
Keywords: G13; 330; exotic options; Heston Model; Characteristic Function; Multidimensional Fast Fourier Transforms; Optionspreistheorie; Volatilität; Stochastischer Prozess; Theorie